UMP won big at ITEX 2013 - Noor Syahidah, Sabran (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) took part in the International Invention, Innovation and Technology Exhibition (ITEX 2013) which was held on May 9-11, 2013 at the Kuala Lumpur Convention Centre.